A Descriptive Study of Matriculation Program: Students’ Responses of Youtube Video as Supplementary Material - Desy Awal Mar’an; Nita Sitta Rachma; Anwar Fadila; Hamida Nur Rahmawati (MUDABBIR Journal Research and Education Studies, 2025)
Matriculation program is a program for first year students. In normal condition, it provides face to face learning and material for students to have good introduction about English for daily life and in oral communication, but after pandemic era the program had to be done via online and the focus was changed to be preparing students to have TOEFL Test.  In this program, the language center did not only provide instructor to deliver material to the students, but they also provided video on Youtube as supplementary material. This is a descriptive study where the researchers explain the result in descriptive way. The sample of this study are matriculation program students. The aims of this study are: 1) To describe the process of matriculation program, 2) To obtain students’ responses about the use of video in Youtube as supplementary material in matriculation program. Interview and documentation were the data collection techniques of this study. The results of this study are: 1) Matriculation program was run using Zoom or Google meet for fourteen meetings and sixty minutes in each meeting. 2) Students thought that the Youtube videos uploaded by language center helped them to remind the material delivered by the instructor, 3) Students suggested that the video should be more creative, add Bahasa Indonesia and more detail explanation.